Enhancing Passenger Satisfaction Through Service Quality: The Strategic Role of Baggage Handling - Marthaleina Ruminda; Purbanuara Parlindungan; Nurul Aulia Salsa Bila; Rayhan Adzikra Fachrurozy (Journal of Social Research, 2025)
Intense competition within the low-cost carrier (LCC) industry has shifted the strategic focus from price superiority towards enhancing service quality and passenger satisfaction. This study aims to analyze the strategic role of the operational process of baggage handling in shaping passenger satisfaction by examining the mediating role of Service Quality. Employing a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, data were collected via a questionnaire from 100 respondents, who were predominantly young passengers (under 25 years old) and university students. The findings indicate that Baggage Handling has a direct, positive, and significant influence on both Service Quality and Customer Satisfaction. Furthermore, Service Quality is also proven to have a positive and significant effect on Customer Satisfaction. The most critical finding is the confirmation of the partial mediating role of Service Quality in the relationship between Baggage Handling and Customer Satisfaction. This result implies that baggage handling possesses a dual role: as a component in shaping service quality perceptions and as a direct driver of satisfaction. For LCC managers, this finding underscores the importance of managing baggage handling as a strategic service touchpoint, with practical implications including investment in automated baggage systems, real-time tracking technology, and staff training programs to effectively enhance passenger satisfaction and competitive advantage.